Brecht and the Bible A Study of Religious Nihilism and Human Weakness in Brecht's Drama of Morality and the City - Murphy, G. Ronald (UNC Studies in the Germanic Languages and Literatures, 1980)
This study identifies the underlying patterns of persistent biblical allusion in the work of renowned playwright Bertolt Brecht. Rather than reducing Brecht's use of the Bible to the purely satirical, the author interprets the full dramatic function of Brecht's complex use of scripture. Using examples from plays written throughout the span of Brecht's career, Murphy shows how Brecht invokes the stories of Old Testament figures such as Job and Isaiah as well as the crucifixion accounts of the New Testament in order to build sympathetic characters and explore his more political themes.